Complex variables : introduction and applications. - Ablowitz, Mark J.; Fokas, Athanassios S. (Cambridge : New York : Cambridge University Press, 2000)
This text provides both an introduction to complex variables and an extensive array of applications, illustrative examples and homework exercises. It is ideal for use in introductory undergraduate and graduate level courses in complex variables
Includes bibliographical references and index.
Keywords: Functions of complex variables